PENINGKATAN VOLUME SEMEN DAN KUALITAS SPERMATOZOA IKAN BETOK (Anabas testudineus Bloch) UNTUK PEMIJAHAN BUATAN DALAM KONSERVASI SUMBERDAYA PERAIRAN - Sukendi Sukendi; Windarti Windarti; Ridwan Manda Putra (Jurnal Ilmu Lingkungan, 2017)
This study aims to determine the increase of cement volume and the quality of fish spermatozoa betok (Anabas testudineus Bloch) by using ovaprim and hCG stimuli for artificial spawning in the conservation of marine resources. The treatment used was P1 = ovaprim injection with dose 0.4 ml / kg body weight, P2 = ovaprim injection with dose 0.6 ml / kg body weight, P3 = injection of hCG with dose 400 IU / kg body weight, P4 = injection hCG with dose of 800 IU / kg body weight and P5 = 1 ml of physiological 0.65% / kg body weight (as control). The parameters measured were the volume of cement, spermatozoa concentration, spermatozoa motility and viability of spermatozoa. The results showed that the best treatment was 0.6 ml ovaprim / kg body weight injection, 0.9 ml of cement volume, spermatozoa concentration of 1250 x 109 cells / ml, spermatozoa viability of 88.90% and spermatozoa motility of 65.40%.